Simulation of CO2 Gas Adsorption Process Flow at Cyclone Gas Outlet in Palm Oil Mills Using Computation Fluid Dynamic Simulation - Novi Sylvia; Yunardi Yunardi; Husni Husni; Abrar Muslim (International Journal of Engineering, Science and Information Technology, 2021)
Cyclone separator is equipment used to control emissions  from gas flow in industrial processes. The principle of removing particulates from the gas flow in this tool is to use the centrifugal force. The centrifugal force generated from the rotating flow will make dust       particles wasted into the cyclone wall where the dust will then fall into the hopper. Adsorption is a series of processes for the accumulation of a substance (adsorbate) on the surface of another substance (adsorbent). Adsorption can occur because of the energy on the surface and the attraction force on the surface. This study aims to obtain a good CO2 adsorption efficiency from modifying the cyclone separator using an adsorption column, analyzing the CO2 gas adsorption process produced from the biomass system at the utility unit boiler station at the Palm Oil Mill (PMO) using a modified cyclone. This simulation was carried out using the Autodesk Inventor Professional 2017 (Student Version) application for the descripction of the tool as a preprocessor and Ansys 2019 R3 (Student Version) applications as a processor and post processor. The variations that were applied included the adsorption column bed height of 3100 mm and 4650 mm, respectively, CO2 gas flow rates of 10, 12.5, 15, 17.5, 20, 22.5 dan 25 m/s and mass loading 0,001 kg/s. The results obtained in the most optimal modification of the cyclone separator are at a bed height of 3100 mm with the highest adsorption percentage 93.437%, the highest flow 91.974% with a pressure drop of 1000 Pa.